The relationship between quality, ethics, performance standards, and their impact on performance quality (an applied study at the University of Thi-Qar) - Dr.Ameen Mohammed Hasan (Journal of College of Education, 2025)
The aims of the study were defined by examining the relationship between quality, ethics, and performance standards and their influence on the quality of performance among professors at Thi-Qar University, as well as taking a broad look at the role of quality management in our educational institutions in order to improve the reality of the educational process. To achieve the aims of the study, the researcher prepared a questionnaire form that included a set of questions, and it was distributed to a group of professors at Thi-Qar University electronically, and the study sample included (40) professors. The descriptive analytical approach was relied upon as it is the appropriate approach for such studies. The study reached a number of conclusions, including, but not limited to: 1. The results of the statistical analysis revealed the existence of a statistically significant relationship between gender and the university by setting a clear plan to improve the quality of academic performance. After conducting the chi-square test to determine the significance of the moral difference between the answers and data provided by the respondents, we found that there was a statistically significant moral difference, because the calculated chi-square test value equals (5.871), which is higher than the tabular chi-square value of (3.841) and at a confidence level of (95%), a significance level of (0.05), and a degree of freedom of (1), so we accept the research hypothesis and reject the null hypothesis. 2. The results of the statistical achievement showed the existence of a statistically significant relationship between years of service and professors’ commitment to performance standards, which is positively reflected in the university’s reputation. After conducting the chi-square test to determine the significance of the moral difference between the answers and data provided by the respondents, we found that there is a statistically significant moral difference, because the calculated chi-square test value is equal to (8.864), which is higher than the tabular chi-square test value of (3.841), and at a reliability level of (95%), a significance level of (0.05) and a degree of freedom of (1), so we accept the research hypothesis and reject the null hypothesis.